(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The synthetic sulfonamide derivative 4-((4-((4-chlorophenyl)imino)-2-hydroxypent-2-en-3- yl)diazenyl)benzenesulfonamide (HPDB) was studied using FT-IR, 13CNMR, and 1H NMR spectroscopy. Potentiometric polarization measurements were used to assess the inhibitory potential of the azoazomethin molecule (HPDB). The presence of a physical adsorption process was corroborated by the thermodynamic features that were experimentally determined, and adsorption followed the "Langmuir" adsorption "isotherm". According to the electrochemical approach, raising the inhibitor concentration in 1M HCl solution enhanced the efficiency of the inhibition. It was also investigated how temperature affected the corrosiveness rate in both the lack of and presence of these chemicals. For the dissolving process, the apparent activation energies, Arrhenius constant, enthalpies, and entropies were calculated and analyzed. For the adsorption process, the free energies and adsorption equilibrium constant were also found and discussed. We gathered crucial knowledge regarding HPDB inhibitory behavior from the basic thermodynamic functions